Model stopnje ogroženosti plazov na osnovi multivariatne analize - Komac, Marko (Geologija, 2004)
Landslide occurrence is governed by numerous spatial and temporal factors thatcan be divided into the causes and the triggers. Human interaction with the environment coincides mainly with the triggers, which are also of natural origin. For a better understanding of the causing factors, which mainly influence the spatial distribution, several methods based on GIS technology are used. Results, derived from these methods, define areas that are more exposed to triggering factors, consequencially also to human activity. Based on the results of the univariate analysis the landslide occurrence specifics of the classes of factors under observation were defined. The interactions among spatial factors were analysed with multivariate statistics and their relative contribution to landslide occurrence were defined. Results were finally presented in the form of probability map (hazard map), and the area ofthe western central part of Slovenia was divided into the danger zones usingfive degree scale.
Keywords: GIS; modeli; napovedovanje; ogroženost; plazovi; prostorski informacijski sistemi; Slovenia; Slovenija; statistične metode